1984
DOI: 10.1177/154079698400900408
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Comparison Study of Cost-Effectiveness: Institutionalized and Deinstitutionalized People

Abstract: Article Descriptorsdeinstitutionalization; cost-effectiveness; community residen tial services; matched comparison; Pennhurst.Seventy people with mental retardation who had moved from a large state institution to small community living arrangements were matched with 70 people who remained at the same institution. They were matched by sex, level of retardation, years institutionalized, selfcare skills, age, and IQ. Developmental growth, opera tionally defined as adaptive behavior change using a research version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Similarly, Lakin, Hill, and Bruininks (1985) reported that Intermediate Care Facilities for People with Mental Retardation (which were dominated by large public institutions) had per diem costs that were 2.8 times higher than private facilities (which were usually community-based). Other investigators came to similar conclusions (Ashbough & Allard, 1983;Baker, Seltzer & Seltzer, 1977;Campbell & Smith, 1989;Conroy & Bradley, 1985;Intagliata, Willer & Cooley, 1979;Jones, Conroy, Feinstein & Lemanowicz, 1984;Minnesota Department of Public Welfare, 1979;Murphy & Datel, 1976;and Touche Ross and Company, 1980). A few dissenters have questioned the accuracy of these comparisons between the cost of community-based residential care and institutional care on the grounds that incomplete cost data has resulted in frequent understatement of the costs of community-based residential facilities (Braddock, 1981;Jones & Jones, 1976;Mayeda & Wai, 1975).…”
mentioning
confidence: 55%
“…Similarly, Lakin, Hill, and Bruininks (1985) reported that Intermediate Care Facilities for People with Mental Retardation (which were dominated by large public institutions) had per diem costs that were 2.8 times higher than private facilities (which were usually community-based). Other investigators came to similar conclusions (Ashbough & Allard, 1983;Baker, Seltzer & Seltzer, 1977;Campbell & Smith, 1989;Conroy & Bradley, 1985;Intagliata, Willer & Cooley, 1979;Jones, Conroy, Feinstein & Lemanowicz, 1984;Minnesota Department of Public Welfare, 1979;Murphy & Datel, 1976;and Touche Ross and Company, 1980). A few dissenters have questioned the accuracy of these comparisons between the cost of community-based residential care and institutional care on the grounds that incomplete cost data has resulted in frequent understatement of the costs of community-based residential facilities (Braddock, 1981;Jones & Jones, 1976;Mayeda & Wai, 1975).…”
mentioning
confidence: 55%
“…Bensberg and Smith (1984) found the average daily costs for group homes to be $8 1.86 per day or $29,878.90 per year. Jones, Conroy, Feinstein, and Lemanowicz (1984), comparing the average costs per year across group homes and institutions, calculated group home costs as $40,284 per year and institutional costs as $47,170. Greenberg, Lakin, Hill, Bruininks, and Hauber (1985) reported that in 1982 small facility models showed considerable variation in cost of care.…”
mentioning
confidence: 99%